2020
DOI: 10.1016/j.chest.2020.08.1513
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Clinical Characteristics of Adult Non-Cystic Fibrosis Bronchiectasis Patients on High Frequency Chest Wall Oscillation and Other Airway Clearance Therapies: Analysis From the United States Bronchiectasis Research Registry

Abstract: Non-Cystic Fibrosis Bronchiectasis (NCFBE) is characterized by permanent dilatation of the airways and a vicious cycle of inflammation, leading to impaired mucous clearance, recurrent infection, and progressive airway damage. Use of Airway Clearance Therapies (ACTs) is part of clinical practice. In this study, we aimed to evaluate the characteristics of adults with NCFBE receiving High Frequency Chest Wall Oscillation (HFCWO) therapy and other ACTs, utilizing the U.S. Bronchiectasis Research Registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…In the current study, the results indicate that physiotherapists are generally following the bronchiectasis guidelines and using the stepwise approach to management: patients are using manual ACTs when they are experiencing milder symptoms, and as their symptoms become more severe, adjunct type ACTs and mucoactives are also being used. Similar results have been shown in the US Bronchiectasis Registry [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the current study, the results indicate that physiotherapists are generally following the bronchiectasis guidelines and using the stepwise approach to management: patients are using manual ACTs when they are experiencing milder symptoms, and as their symptoms become more severe, adjunct type ACTs and mucoactives are also being used. Similar results have been shown in the US Bronchiectasis Registry [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…Data from the EMBARC registry [ 15 ] found that only 48.3% of patients performed ACTs regularly with the primary reason for not doing ACTs being that it was not required in the opinion of the clinicians (67.9%). Data from the US Bronchiectasis Registry [ 16 ] found that more than one-half of patients (58%) who used ACTs at baseline did not report the use of ACTs at 1-year follow-up. In contrast, in the current survey, 78% of patients reported performing the same type of ACT at 9–12 months follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the adherence to ACTs in the UK population appeared to be high. Upon completion of the first survey, 86% (177 out of 205) of patients still performed ACTs, and in the second survey, 78% (70 out of 90) of patients reported performing the same type of ACT, which was markedly higher than the adherence in the US Bronchiectasis and Non-tuberculous Mycobacteria Registry, in which only a quarter adhered to ACTs at the 1-year follow-up [ 14 ]. The current findings remained more reassuring when compared with the adherence (41% of patients continuously adopted ACTs) in Northern Ireland according to the statistics reported in another study [ 14 ].…”
mentioning
confidence: 99%
“…In the current survey, 68% (140 out of 205) of patients reported that the initial ACT practice was guided by a physiotherapist during an outpatient visit and that most patients thought that visiting a physiotherapist specialising in bronchiectasis management would be crucial for guiding their initial use of ACTs. Besides, the active cycle of breathing technique (64%, 129 out of 201 patients) was the most commonly reported ACT manoeuvre, followed by huffing (41%), and exercise and/or physical activity (38%), which differed from the findings of the US Bronchiectasis and Non-tuberculous Mycobacteria Registry and an Australian ACT study among patients with cystic fibrosis [ 12 , 14 ]. The use of ACT might vary globally depending on the culture and the patient's preference, and there is currently no high-quality evidence that is directly driven from head-to-head comparisons of different ACT manoeuvres [ 7 , 16 ].…”
mentioning
confidence: 99%